Effects of Different Modification Methods on the Properties of Sisal Fibers - Mingming Wu; Zhanying Sun; Xiongyan Zhao (Journal of Natural Fibers, 2020)
In this paper, sisal fibers were modified by different methods such as alkali treatment, γ-aminopropyltriethoxysilane treatment, tetraethylorthosilicate (TEOS) sol-gel treatment, TEOS, and silane combination treatment. The effects of different modification methods on the properties of sisal fibers were studied by thermogravimetric analysis (TGA), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and universal material testing machine. The results show that the combination treatment fiber has the best heat resistance and the most obvious improvement in tensile properties, the tensile strength and modulus increase by 31.58% and 15.82%, respectively.